Serum YKL-40 as Candidate Biomarker in Sepsis-Induced Lung Injury - Ateş, Gülten; Yorulmaz, Hatice; Özkök, Elif; Tamer, Şule (Cerrahpaşa Medical Journal, 2023)
Objective: Sepsis is a phenomenon with a higher mortality rate and a higher incidence and its mechanism has not been fully elucidated yet. Oxidative damage is also known to be responsible for damage and mortality in sepsis. In recent years, simvastatin has been reported to be used for the treatment of sepsis and had many pleiotropic effects such as antioxidant and anti-in%ammatory. It is demonstrated that chitinase-3-like protein 1 exerts its func- tion in infection. Recent studies have proposed that chitinase-3-like protein 1 may be an indicator of sepsis. Methods: The effect of simvastatin on chitinase-3-like protein 1 and antioxidant enzymes, glutathione reductase, glutathione peroxidase, superoxide dismutase in rats which formed as control, lipopolysaccharide, simvastatin, and simvastatin+lipopolysaccharide groups was examined.Serum and lung tissue Chitinase-3-like protein 1 levels, which may be an early biomarker in sepsis were investigated. Serum glutathione reductase, glutathione peroxidase, and superoxide dismutase were evaluated as oxidative stress parameters. Also, lung tissues were histologically examined with hematoxy- lin and eosin staining. Results: Lung chitinase-3-like protein 1 was improved in the simvastatin+lipopolysaccharide group comparing lipopolysaccharide, meanwhile, serum chitinase-3-like protein 1 was elevated in the lipopolysaccharide group (p<0.05), and pretreated of simvastatin was to be reduced YKL-40 levels. In the lipopolysaccharide group, decreased serum glutathione reductase (P < .01), glutathione peroxidase (P < .01), and superoxide dismutase (P < .01) were found to be consumed against oxidative stress, and in the simvastatin+lipopolysaccharide group, increased glutathione reduc- tase and glutathione peroxidase were obtained (P < .01). We observed histological damage in the lipopolysaccharide and improved injury in the simvastatin+lipopolysaccharide as similar simvastatin and controls. Conclusions: Simvastatin may be effective on sepsis and protective against in%ammation and oxidative stress. This study proposed that chitinase-3-like protein 1 may be an indicator candidate for sepsis. Cite this article as: AteÎ G, Özkök E, Yorulmaz H, Tamer Î. Serum YKL-40 as candidate biomarker in sepsis-induced lung injury. CerrahpaÎa Med J. 2023;47(2):156-161.